The Efficacy of Instagram @Gurukumrd as the Media in Improving Students’ Reading Skills - Rizqy Dienillah Fitrina Putri; Muhamad Sofian Hadi; Mutiarani Mutiarani (Journal of Languages and Language Teaching, 2021)
Instagram is an online mobile photo and video sharing that can attract students’ attention in the learning process. It is also used to interact and share stories to others directly. Because of this, Instagram is a social media which can be utilized to navigate students to read. This study aims to find out the use of Instagram @gurukumrd to improve students’ reading skills. The Instagram @gurukumrd is chosen as the object of this study because it provides students with reading activities through stories, comments, and opinions. To reach the aim of this study, researchers employed qualitative research with Ethnography method. The data are collected using instruments which are observation sheets and interview guidelines. There are 37 students involved in this study as respondence. Based on the research findings, the Instagram @gurukumrd facilitates students to acquire various vocabulary and grammatical knowledge. In addition, students acquire competencies on how to gain paragraph ideas, topic sentences, and reading comprehension. Through Instagram, students can remember and recognize difficult words. At the end of this, this media facilitates students to read simple paragraphs quickly. Based on the research findings, this study can conclude that the Instagram @gurukumrd can facilitate students to enhance students’ reading skills.